Secure Cloud Storage: A Protocol for Remote Data Integrity Checking - S, Naganandhini.; S.T, Shenbagavalli.; M., Shanmugapriya. (IJRDO -Journal of Computer Science Engineering, 2016)
The integrity of files stored on servers is crucial for many applications running on the internet. Recently, many works provide data dynamics and/or public verifiability to this type of protocols. Remote data possession checking protocols permit checking that, a remote server can access an uncorrupted file in such a way that a verifier does not need to know beforehand the entire file. In addition, both data dynamics operations and public verifiability are supported. Token pre-computation algorithm is used to generate tokens. Challenge-Response protocol is used for communication between the challenger and the responder. Through a formal analysis, the correctness and security of the protocol is shown. After that, through theoretical analysis and experimental results, we demonstrate that the proposed protocol has a good performance.